2006
DOI: 10.1116/1.2333571
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reactive ion etching of dielectrics and Si in CHF3∕O2 or CHF3∕Ar for photovoltaic applications

Abstract: Using a combination of etch rate, photoconductance, and deep level transient spectroscopy ͑DLTS͒ measurements, the authors have investigated the use of reactive ion etching ͑RIE͒ of dielectrics and Si in CHF 3 /O 2 and CHF 3 / Ar plasmas for photovoltaic applications. The radio frequency power ͑rf-power͒ and gas flow rate dependencies have shown that the addition of either O 2 or Ar to CHF 3 can be used effectively to change the etch selectivity between SiO 2 and Si 3 N 4. The effective carrier lifetime of sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…2(b)) and this can be important in reducing the surface scattering loss of the fabricated waveguide. A low LER of the patterned PR resulted from employing the BARC as well as teflon-like polymer passivation on the sidewall in CHF 3 plasma [9]. The details of this issue will be dealt in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 96%
“…2(b)) and this can be important in reducing the surface scattering loss of the fabricated waveguide. A low LER of the patterned PR resulted from employing the BARC as well as teflon-like polymer passivation on the sidewall in CHF 3 plasma [9]. The details of this issue will be dealt in a forthcoming paper.…”
Section: Resultsmentioning
confidence: 96%
“…It is noted that for etching substrate, as shown in Fig. 2(a), S g,eff is different from typical surface recombination velocity S g at Si/SiO 2 interface since it involves the component of carrier diffusion from all of the outer depletion regions, where the effective carrier lifetime is degraded by surface defects [7], [15], [16]. For RIE-induced interface traps, the various density distributions in energy throughout the silicon bandgap lead to the complexity in calculating S g .…”
Section: A Minority Carrier Profilementioning
confidence: 99%
“…For example, interface traps along the channel of MOSFETs result in the reduction of drive current and the increase of leakage current as well as power consumption [13], [14]. Besides, it was found that the generation lifetime was degraded by RIE using pulsed metal-oxidesemiconductor (MOS) capacitance method [7], [15]- [17]. It is well known that interface traps either under gate or within depletion region from the gate edge contribute to gate current by generation-recombination process [14], [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the interaction with plasma potentiality could induce the degradation of silicon substrate during the dry etching process . During RIE, high‐energy ions from the plasma attack the silicon surface and create a subsurface defect region in the depth of several microns . In a previous study, a detailed study of silicon surface damage caused by RIE has been investigated.…”
Section: Introductionmentioning
confidence: 99%